2007
DOI: 10.1002/app.26368
|View full text |Cite
|
Sign up to set email alerts
|

Removal of formaldehyde at low concentration using various activated carbon fibers

Abstract: Adsorption of low concentration formaldehyde on pitch-based, rayon-based, and PAN-based activated carbon fibers (ACFs) and an unactivated PAN-based carbon fiber (PAN-CF) was investigated by a dynamic method. The pore structure and surface chemistry of these samples were characterized by liquid nitrogen adsorption, elemental analysis, and X-ray photoelectron spectroscopy. Results revealed that the pore structure, especially surface chemical composition, greatly influence the formaldehyde adsorption. PANbased AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 9 publications
2
62
0
Order By: Relevance
“…In particular, the peak intensity at 1,650 cm −1 was increased when the char was treated with both KOH and ammonia (SCK+SCA), which was attributed to the growth of the C=O peak as a result of the KOH treatment and the growth of the nitrogen functional group peak as a result of the ammonia treatment. Various functional groups, including, in particular, those of oxygen and nitrogen, are known to affect the formaldehyde adsorption performance [4][5][6]8,10]. Fig.…”
Section: Adsorption Of Formaldehyde Over Sludge Charmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the peak intensity at 1,650 cm −1 was increased when the char was treated with both KOH and ammonia (SCK+SCA), which was attributed to the growth of the C=O peak as a result of the KOH treatment and the growth of the nitrogen functional group peak as a result of the ammonia treatment. Various functional groups, including, in particular, those of oxygen and nitrogen, are known to affect the formaldehyde adsorption performance [4][5][6]8,10]. Fig.…”
Section: Adsorption Of Formaldehyde Over Sludge Charmentioning
confidence: 99%
“…However, research on adsorbents which remove indoor formaldehyde from air remains insufficient. Song et al [5] investigated low concentration formaldehyde removal using pitch-based, rayon-based, and PANbased activated carbon fibers. They reported that the PAN-based activated carbon fiber gave the best adsorption performance for the removal of formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption capacity of ACFs for formaldehyde is not effective in ambient air either (Economy et al 1992), owing to the weak interaction between polar formaldehyde and the hydrophobic surface of porous carbon (Ozaki and Oya 1997). Song et al (2007) studied the removal of formaldehyde at low concentration using various activated carbon fibers and found that polyacrylonitrile (PAN)-ACF showed the greatest formaldehyde adsorption capacity, while the formaldehyde adsorption capacity of Rayon-based ACF was less than expected and lower than needed.…”
Section: Introductionmentioning
confidence: 97%
“…Song et al. [31] tested the formaldehyde removal performance by various ACFs, and they concluded that surface chemical composition, especially nitrogen-containing groups (in PAN-based ACF), significantly promoted the adsorption of formaldehyde. In another work, Virote et al [32] tested six type of coffee residue based activated carbon, and found that ZnCl 2 and CZn-N 2 impregnated activated carbon shows the largest formaldehyde adsorption capacity because of the hydrophilic functional group of O-H, C = O, C-O on the sur- face.…”
Section: Introductionmentioning
confidence: 98%